Щелкунчик и Мышиный Король: сказка / Э. Т. А. Гофман - Гофман Эрнст Теодор Амадей (Внеклассное чтение, 2017)
Экземпляры: (20190708) / Инвентарный номер: 40420 / Цена: 75.60 / Сис.шифр: И / Авт.знак: Г 74 / ГРНТИ: 17.82.93 / ББК: 84(4Гем)